2022
DOI: 10.1038/s41467-022-31488-w
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous and acral melanoma cross-OMICs reveals prognostic cancer drivers associated with pathobiology and ultraviolet exposure

Abstract: Ultraviolet radiation (UV) is causally linked to cutaneous melanoma, yet the underlying epigenetic mechanisms, known as molecular sensors of exposure, have not been characterized in clinical biospecimens. Here, we integrate clinical, epigenome (DNA methylome), genome and transcriptome profiling of 112 cutaneous melanoma from two multi-ethnic cohorts. We identify UV-related alterations in regulatory regions and immunological pathways, with multi-OMICs cancer driver potential affecting patient survival. TAPBP, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…There are only a few known clinico-genomic factors predicting prognosis in CM ( Gerami et al, 2015 ; Cancer Genome Atlas Network, 2015 ; Garg et al, 2021 ). Our data are consistent with those of previous studies that demonstrated the prognostic implication of the UV signature ( Trucco et al, 2019 ; Pham et al, 2020 ; Vicente et al, 2022 ). One of the characteristics of the UV-low cluster is lower mutational and higher CNA burdens, which is similar to the genomic profiles of acral melanoma, a rare subtype of melanoma that has a poorer prognosis than CM ( Liang et al, 2017 ; Rabbie et al, 2019 ; Newell et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…There are only a few known clinico-genomic factors predicting prognosis in CM ( Gerami et al, 2015 ; Cancer Genome Atlas Network, 2015 ; Garg et al, 2021 ). Our data are consistent with those of previous studies that demonstrated the prognostic implication of the UV signature ( Trucco et al, 2019 ; Pham et al, 2020 ; Vicente et al, 2022 ). One of the characteristics of the UV-low cluster is lower mutational and higher CNA burdens, which is similar to the genomic profiles of acral melanoma, a rare subtype of melanoma that has a poorer prognosis than CM ( Liang et al, 2017 ; Rabbie et al, 2019 ; Newell et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the key genomic alterations of acral melanomas described in a previous study ( Newell et al, 2020 ) (such as the highest proportion of triple-WT tumors, common KIT alterations, and lower frequencies of BRAF/RAS hotspot mutations) are consistent with the characteristics of the UV-low cluster in this study. In line with our findings, another recent study reported results from epigenomic mapping which also suggest that UV-low CMs more closely resemble acral melanomas rather than UV-high CMs ( Vicente et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations